Reuse of Elisa plates: development of a simple cleaning method - Manandhar, H.K.; Albrechtsen, S.E.; Mathur, S.B. (Copenhagen (Dinamarca), 1996)
Sumario (En)
6 ref.
Keywords: VIROSIS; ENFERMEDADES DE LAS PLANTAS; CONTROL DE ENFERMEDADES; INCUBACION